A kind of thermosensitive hydrogel material and preparation method thereof
By adding gum arabic and citric acid to chitosan hydrogel and using glutaraldehyde as a crosslinking agent, the problem of hard and brittle structure of chitosan hydrogel is solved, and its mechanical properties and biocompatibility are improved. It is suitable for tissue repair and drug carrier applications.
Patent Information
- Application Number
- CN202210800609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-08
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-07-08
AI Technical Summary
The skeleton structure of pure chitosan hydrogel is too hard and brittle, and has poor mechanical properties, which limits its application in tissue engineering.
Modify chitosan hydrogel by adding gum arabic and citric acid, combining glutaraldehyde as a crosslinking agent, to improve its mechanical strength and ductility.
Hydrogel materials with good biocompatible, mechanical strength and temperature-sensitive response were obtained, improving their performance in tissue repair and drug carrier applications.
Smart Images

Figure CN114989462B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterial preparation, and specifically relates to a temperature-sensitive hydrogel material and a preparation method thereof. Background Art
[0002] Hydrogel is a high molecular polymer material with a unique three-dimensional network structure and water as the dispersion medium. It can absorb water tens or even hundreds of times larger than itself, can swell significantly without dissolving in the aqueous solution, and can also maintain the original structure of the material. Hydrogel has high water content, three-dimensional structure, adjustable mechanical properties and minimally invasive delivery capabilities. It also has the advantages of biodegradability, biocompatibility, wide sources, low cost, and easy large-scale production and preparation. It is a very promising type of tissue regeneration material.
[0003] With the rapid development of life sciences, due to the unique advantages of functional natural polymer hydrogels in biodegradability, biocompatibility, material sources and production, more and more research is being conducted in multiple application fields. As a potential repair material, hydrogels are often used in soft tissue repair. They can also accelerate the repair of different tissues and promote the ability of wound contraction and healing. They are also used in wound dressing applications. In addition, they are also very suitable for local injection therapy as drug carriers.
[0004] Chitosan (CS) is an amino-containing polysaccharide that is widely found in arthropod bones. Its structure is similar to that of naturally occurring glycosaminoglycans and is biodegraded by enzymes in the human body. CS has good biodegradability, biocompatibility, and antibacterial properties and has been widely used in the field of drug delivery. However, the rapid degradation characteristics and poor mechanical properties of CS limit its application range. Therefore, CS as a hydrogel medical material usually needs to be compounded with other materials to improve its performance.
[0005] Since the skeleton structure of pure chitosan hydrogels is often too hard and brittle, they will break when subjected to force and have poor mechanical properties, which limits their application in tissue engineering. Summary of the invention
[0006] Since the hydrogel structure is similar to the extracellular matrix of various tissues and can be delivered under arthroscopy, its properties can be adjusted according to the application needs, such as its composition, cross-linking degree, cross-linking method and cell density. Ideally, the hydrogel material can perfectly mimic the extracellular matrix, especially in load-bearing joints to withstand mechanical pressure and load.
[0007] In order to overcome the technical problems in the prior art that the skeleton structure of pure chitosan hydrogel is often too hard and brittle, will break when subjected to force, and has poor mechanical properties, the present invention increases its flexibility by adding gum arabic and citric acid for composite modification, overcomes the shortcomings of single chitosan hydrogel, and makes it have better mechanical strength and ductility.
[0008] Compared with the prior art, the present invention uses chitosan, anhydrous citric acid and gum arabic, and glutaraldehyde as a cross-linking agent to improve the mechanical properties of the hydrogel through chemical cross-linking, thereby obtaining a hydrogel with good biocompatibility, certain mechanical strength and intelligent response to temperature.
[0009] Anhydrous citric acid is a tribasic acid that plays a very important role in biological metabolism. Citric acid is an edible acid that can enhance normal metabolism in the body. At the same time, citric acid has antioxidant and anti-inflammatory effects and can serve as a cross-linking site for both physical and chemical cross-linking.
[0010] Gum Arabic is the secretion of the gum Arabic tree, and is named after the fact that it is mostly produced in Arab countries. Gum Arabic is a natural polysaccharide polymer that has the advantages of wide sources, safety, renewable and biodegradable. It has good physical and chemical properties and is widely used in food, medicine, papermaking and textile industries, and has broad application prospects.
[0011] In order to achieve the above object, the present invention provides a thermosensitive hydrogel material, which is a chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel material, wherein the mass percentages of chitosan, anhydrous citric acid and gum arabic are 50-85%: 5-10%: 5-45% respectively.
[0012] A method for preparing a thermosensitive hydrogel material, the method comprising the following steps:
[0013] (1) adding chitosan to a dilute acetic acid solution, stirring and ultrasonically dispersing the solution to obtain a solution A;
[0014] (2) adding anhydrous citric acid to solution A and heating in a water bath to obtain solution B;
[0015] (3) dissolving gum arabic in deionized water to obtain solution C;
[0016] (4) adding solution C to solution B, blending and dispersing, and heating in a water bath to obtain solution D, which is then poured into a 24-well plate, and a cross-linking agent is added and allowed to stand to obtain a chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel material;
[0017] In the above technical solution, further, in the step (1), the chitosan has a deacetylation degree of 85-99% and a molecular weight of 1 million.
[0018] In the above technical solution, further, the mass fraction of the dilute acetic acid in step (1) is 0.5-3%.
[0019] In the above technical solution, further, the anhydrous citric acid in step (2) is analytically pure with a purity of more than 99.5%.
[0020] In the above technical solution, further, in the step (3), the gum arabic is in amber granular form and is of medical grade.
[0021] In the above technical solution, further, in the step (4), the mixing stirring speed is 500-1000 r / min, the water bath heating temperature is 40-70° C., and the stirring time is 8-12 h.
[0022] In the above technical scheme, further, the cross-linking agent is any one of glutaraldehyde aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) / 2-(N-morpholino)ethanesulfonic acid (MES) solution of N-hydroxysuccinimide (NHS), and genipin.
[0023] The present invention adds a 2.5% mass fraction of glutaraldehyde aqueous solution or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) / N-hydroxysuccinimide (NHS) 2-(N-morpholino)ethanesulfonic acid (MES) solution or genipin to solution D, so that citric acid and chitosan undergo amide reaction, and the overall cross-linking degree of the hydrogel is improved. The addition of gum arabic can improve the brittleness of the hydrogel, and finally a homogeneous and tough thermosensitive hydrogel composite is obtained.
[0024] The beneficial effects of the present invention are:
[0025] Chitosan has excellent hydrophilicity and high bioadhesion, so the present invention uses chitosan as a hydrogel material, which can make it have good porosity and water swelling, so that the chitosan hydrogel has good tissue compatibility. The introduction of citric acid can effectively reduce the body's inflammatory response, and the addition of gum arabic as a thickener increases the viscosity of the hydrogel, making it more elastic after molding and less prone to brittle cracking.
[0026] The preparation method of the present invention does not generate pollutants, is green and environmentally friendly, and is easy to operate; the prepared hydrogel material is cross-linked to form chemical bonds, which can better disperse the force of the hydrogel and have good mechanical properties, and has also been greatly improved in terms of strength, biocompatibility, etc., and has temperature sensitivity. The hydrogel with good mechanical properties can also increase self-healing properties or recovery properties, which provides convenience for its clinical use. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the infrared spectrum of the chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel prepared in Example 1;
[0028] Figure 2 This is a sample picture of the chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel prepared in Example 1;
[0029] Figure 3 This is a graph showing the effect of temperature on the swelling properties of the thermosensitive hydrogel prepared in Example 1;
[0030] Figure 4 This is a diagram of the mechanical properties of the thermosensitive hydrogel prepared in the present invention. DETAILED DESCRIPTION
[0031] The following examples are provided to facilitate a better understanding of the present invention, but are not intended to limit the present invention. In addition, in the following examples, unless otherwise specified, all materials and reagents used can be purchased from biological or chemical reagent companies.
[0032] Example 1
[0033] (1) Weigh 2 g of chitosan with a deacetylation degree of ≥95% and a molecular weight of 1 million, dissolve it in 100 mL of 2% dilute acetic acid solution in a 60°C water bath and stir for 1 h;
[0034] (2) Then weigh 0.2 g of anhydrous citric acid and add it to the solution obtained in step 1, continue stirring for 1 h, and set the stirring speed to 500 r / min;
[0035] (3) Weigh 2 g of gum arabic and dissolve it in 10 mL of deionized water to prepare a 20% gum arabic solution. Add 5 mL to the solution obtained in step 2, stir mechanically for 8 h at a rate of 500 r / min, and heat in a water bath at 35°C. Then pour the blend into a 24-hole (26×26×26 mm) mold, cool to room temperature, and slowly drip 1 mL of 2.5% glutaraldehyde solution. After cross-linking, chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel is prepared.
[0036] After the experiment, the infrared absorption of the hydrogel was measured by the potassium bromide tablet method. Figure 1 This is the infrared spectrum of the chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel prepared in Example 1. It can be seen from this that Figure 1 In (a) and (c), 3200-3600 cm -1 The broad peak in the region is the absorption peak of the OH bond between CS and gum arabic, 1760 cm -1 It is the C=O stretching vibration peak on the gum arabic molecular chain. Figure 1 In (b), the wave number of citric acid is 3500 cm-1 The absorption peaks of -COOH are 1721 and 1683 cm -1 It is the C=O stretching vibration absorption peak, and 1406 is the coupling of the in-plane bending vibration of citric acid -OH and the CO stretching vibration. Figure 1 (c), 1117 and 1090 cm -1 The peaks are the COC stretching vibration and the CO antisymmetric and symmetric stretching vibration peaks on the CS polysaccharide ring structure. Figure 1 (d) 1750 and 1590 cm -1 The absorption peaks at the bottom and bottom are amide I and II bonds, respectively. The formation of amide bonds can be observed, indicating that an amidation reaction occurs between citric acid and chitosan.
[0037] Figure 2 This is a sample of the chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel prepared in Example 1. Figure 2 As can be seen from (a), the hydrogel prepared by this method is a yellow gel with uniform shape and smooth surface. The size of the gel is 25×25×15 mm. A simple load-bearing test is performed on it. A 50 g weight is placed on the top of the gel and its deformation is recorded. Figure 2 As can be seen in (b), when the hydrogel undergoes a displacement of 5 mm, it can withstand a certain pressure and maintain its original shape without breaking.
[0038] Figure 3 The effect of temperature on the swelling performance of the hydrogel prepared in Example 1 is shown in the figure. The prepared hydrogel was weighed, immersed in a beaker filled with distilled water, and sealed with plastic wrap, and then placed in an oven at 5°C, 25°C, 35°C, 45°C and 65°C respectively. The water on the surface was wiped out and weighed every 30 minutes until the mass of the hydrogel remained unchanged, and the maximum water absorption swelling degree of the hydrogel at different temperatures was calculated. It can be seen that when the temperature rises from 5°C to 25°C, the saturated swelling degree increases; the saturated swelling rate decreases as the temperature continues to rise. When 25°C, the maximum swelling rate is reached. This is because when the temperature is low, as the temperature rises, the molecular chain movement intensifies, the network structure expands, the volume expands, and it is easy to combine with water molecules through intermolecular forces such as hydrogen bonds, so that the absorption rate increases; when the temperature continues to rise, the random thermal motion of water molecules intensifies, and the attraction force between the hydrogel molecular structure and water molecules decreases, so that the water absorption rate decreases and the saturated swelling degree decreases.
[0039] Example 2
[0040] (1) Weigh 2 g of chitosan with a deacetylation degree of ≥95% and a molecular weight of 1 million, dissolve it in 100 mL of 2% dilute acetic acid solution in a 60°C water bath and stir for 1 h;
[0041] (2) Then weigh 0.2 g of anhydrous citric acid and add it to the solution obtained in step 1, continue stirring for 1 h, and set the stirring speed to 500 r / min;
[0042] (3) Weigh 2 g of gum arabic and dissolve it in 10 mL of deionized water to prepare a 20% gum arabic solution. Add 1 mL to the solution obtained in step 2, stir mechanically for 8 h at a rate of 500 r / min, and heat in a water bath at 35°C. Then pour the blend into a 24-hole (26×26×26 mm) mold, cool to room temperature, and slowly drip 1 mL of 2.5% glutaraldehyde solution. After cross-linking, chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel is prepared.
[0043] Example 3
[0044] (1) Weigh 2 g of chitosan with a deacetylation degree of ≥95% and a molecular weight of 1 million, dissolve it in 100 mL of 2% dilute acetic acid solution in a 60°C water bath and stir for 1 h;
[0045] (2) Then weigh 0.2 g of anhydrous citric acid and add it to the solution obtained in step 1, continue stirring for 1 h, and set the stirring speed to 500 r / min;
[0046] (3) Weigh 2 g of gum arabic and dissolve it in 10 mL of deionized water to prepare a 20% gum arabic solution. Add 3 mL to the solution obtained in step 2, stir mechanically for 8 h at a rate of 500 r / min, and heat in a water bath at 35°C. Then pour the blend into a 24-hole (26×26×26 mm) mold, cool to room temperature, and slowly drip 1 mL of 2.5% glutaraldehyde solution. After cross-linking, chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel is prepared.
[0047] Example 4
[0048] (1) Weigh 2 g of chitosan with a deacetylation degree of ≥95% and a molecular weight of 1 million, dissolve it in 100 mL of 2% dilute acetic acid solution in a 60°C water bath and stir for 1 h;
[0049] (2) Then weigh 0.2 g of anhydrous citric acid and add it to the solution obtained in step 1, continue stirring for 1 h, and set the stirring speed to 500 r / min;
[0050] (3) Weigh 2 g of gum arabic and dissolve it in 10 mL of deionized water to prepare a 20% gum arabic solution. Add 7 mL to the solution obtained in step 2, stir mechanically for 8 h at a rate of 500 r / min, and heat in a water bath at 35°C. Then pour the blend into a 24-hole (26×26×26 mm) mold, cool to room temperature, and slowly drip 1 mL of 2.5% glutaraldehyde solution. After cross-linking, chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel is prepared.
[0051] Example 5
[0052] (1) Weigh 2 g of chitosan with a deacetylation degree of ≥95% and a molecular weight of 1 million, dissolve it in 100 mL of 2% dilute acetic acid solution in a 60°C water bath and stir for 1 h;
[0053] (2) Then weigh 0.2 g of anhydrous citric acid and add it to the solution obtained in step 1, continue stirring for 1 h, and set the stirring speed to 500 r / min;
[0054] (3) Weigh 2 g of gum arabic and dissolve it in 10 mL of deionized water to prepare a 20% gum arabic solution. Add 9 mL to the solution obtained in step 2, stir mechanically for 8 h at a rate of 500 r / min, and heat in a water bath at 35°C. Then pour the blend into a 24-hole (26×26×26 mm) mold, cool to room temperature, and slowly drip 1 mL of 2.5% glutaraldehyde solution. After cross-linking, chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel is prepared.
[0055] Example 6
[0056] (1) Weigh 2 g of chitosan with a deacetylation degree of ≥95% and a molecular weight of 1 million, dissolve it in 100 mL of 2% dilute acetic acid solution in a 60°C water bath and stir for 1 h;
[0057] (2) Then weigh 0.2 g of anhydrous citric acid and add it to the solution obtained in step 1, continue stirring for 1 h, and set the stirring speed to 500 r / min;
[0058] (3) No gum arabic was added to the solution obtained in step 2, and mechanical stirring was performed for 8 h at a rate of 500 r / min. At the same time, water bath heating was performed at a temperature of 35°C. The mixture was then poured into a 24-hole (26×26×26 mm) mold, and after cooling to room temperature, 1 mL of 2.5% glutaraldehyde solution was slowly dripped into it. After cross-linking, chitosan / anhydrous citric acid thermosensitive hydrogel was prepared.
[0059] Figure 4The mechanical properties of the thermosensitive hydrogel prepared by the present invention are shown in Figure 1. The mechanical properties of the hydrogel prepared by the present invention are analyzed by applying a load above the hydrogel, with a displacement of 4mm as the standard. As can be seen from the figure, when the amount of gum arabic added is 1-9mL, the load-bearing capacity of the chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel is 70, 75, 80, 100 and 65g respectively, which is significantly improved compared to the mechanical properties of the chitosan / anhydrous citric acid thermosensitive hydrogel. The addition of gum arabic improves the toughness of the hydrogel to a certain extent, and can bear 100g when adding 5mL. At this time, the interaction between the crosslinking agent and the polymer chain is the strongest, and the network structure is tighter, so the compression performance is the best.
[0060] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.
Claims
1. A thermosensitive hydrogel material, characterized in that: The invention is a chitosan / anhydrous citric acid / arabic gum temperature-sensitive hydrogel material, wherein the mass percentages of chitosan, anhydrous citric acid and arabic gum are 50-85%: 5-10%: 5-45% respectively.
2. A method for preparing a thermosensitive hydrogel material, characterized in that: The method comprises the following steps: (1) adding chitosan to a dilute acetic acid solution, stirring and ultrasonically dispersing the solution to obtain a solution A; (2) adding anhydrous citric acid to solution A and heating in a water bath to obtain solution B; (3) dissolving gum arabic in deionized water to obtain solution C; (4) adding solution C to solution B, blending and dispersing, and heating in a water bath to obtain solution D, which is then poured into a 24-well plate, and a cross-linking agent is added and allowed to stand to obtain a chitosan / anhydrous citric acid / gum arabic thermosensitive hydrogel material; In the step (4), the mixing speed is 500-1000 r / min, the water bath heating temperature is 40-70° C., and the mixing time is 8-12 h; The cross-linking agent is any one of glutaraldehyde aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) / N-hydroxysuccinimide (NHS) 2-(N-morpholino)ethanesulfonic acid (MES) solution, and genipin; The mass fraction of the glutaraldehyde aqueous solution is 2.5%.
3. The method for preparing a thermosensitive hydrogel material according to claim 2, characterized in that: In the step (1), the deacetylation degree of chitosan is 85-99% and the molecular weight is 1 million.
4. The method for preparing a thermosensitive hydrogel material according to claim 2, characterized in that: The mass fraction of the dilute acetic acid in step (1) is 0.5-3%.
5. The method for preparing a thermosensitive hydrogel material according to claim 2, characterized in that: The anhydrous citric acid in step (2) is analytically pure, with a purity of more than 99.5%.
6. The method for preparing a thermosensitive hydrogel material according to claim 2, characterized in that: In the step (3), the gum arabic is in amber granular form and is of medical grade.
Citation Information
Patent Citations
Citric acid cross-linked chitosan hydrogel and preparation method thereof
CN108341977A
High shape recovery rate hydrogel and preparation method thereof
CN110551298A